Hybridization in palms (Arecaceae) - Christine D. Bacon; Adrian Hill (Ecology and Evolution, 2024)
Abstract Hybridization has significant evolutionary consequences across the Tree of Life. The process of hybridization has played a major role in plant evolution and has contributed to species richness and trait variation. Since morphological traits are partially a product of their environment, there may be a link between hybridization and ecology. Plant hybrid species richness is noted to be higher in harsh environments, and we explore this hypothesis with a keystone tropical plant lineage, palms (Arecaceae). Leveraging a recent literature review of naturally occurring palm hybrids, we developed a method to calculate hybrid frequency, and then tested if there is phylogenetic signal of hybrids using a phylogeny of all palms. Further, we used phylogenetic comparative methods to examine the interaction between hybrid frequency and presence in dry environments, on islands, and the species richness of genera. Phylogenetic generalized least squares models had stronger support than models of random association, indicating phylogenetic signal for the presence of hybrids in dry and island environments. However, all p‐values were >.05 and therefore the correlation was poor between hybridization and the trait frequencies examined. Presence in particular environments are not strongly correlated to hybrid frequency, but phylogenetic signal suggests a role in its distribution in different habitats. Hybridization in palms is not evenly distributed across subfamilies, tribes, subtribes yet plays an important role in palm diversity, nonetheless. Increasing our understanding hybridization in this economically and culturally important plant family is essential, particularly since rates are projected to increase with climate change, reconfiguring the dynamics and distribution of biodiversity.